Severe Aplastic Anemia following Acute Hepatitis from Toxic Liver Injury: Literature Review and Case Report of a Successful Outcome - Kamran Qureshi; Usman Sarwar; Hicham Khallafi (Case Reports in Hepatology)
Hepatitis associated aplastic anemia (HAAA) is a rare syndrome in which severe aplastic anemia (SAA) complicates the recovery of acute hepatitis (AH). HAAA is described to occur with AH caused by viral infections and also with idiopathic cases of AH and no clear etiology of liver injury. Clinically, AH can be mild to fulminant and transient to persistent and precedes the onset SAA. It is assumed that immunologic dysregulation following AH leads to the development of SAA. Several observations have been made to elucidate the immune mediated injury mechanisms, ensuing from liver injury and progressing to trigger bone marrow failure with the involvement of activated lymphocytes and severe T-cell imbalance. HAAA has a very poor outcome and often requires bone marrow transplant (BMT). The findings of immune related myeloid injury implied the use of immunosuppressive therapy (IST) and led to improved survival from HAAA. We report a case of young male who presented with AH resulting from the intake of muscle building protein supplements and anabolic steroids. The liver injury slowly resolved with supportive care and after 4 months of attack of AH, he developed SAA. He was treated with IST with successful outcome without the need for a BMT.